A Survey Study on the Defects Found in Low-Income Housing: Case Study Seongnam City Korea. Issue 1 (1st March 2017) - Ko, Bong-Kuk; Lee, Woo-Jung; Lee, Jae-Hoon
Abstract : The purpose of this study is to understand what health and safety hazards low-income households are subject to by surveying the real conditions of the defective housing of low-income households, and to find improvement strategies. For this purpose, we visited the concentrated areas of the multi-dwelling unit (MDU) (also known as multi-family residential) housing in Jungwon-gu and Sujeong-gu in Seongnam City, Kyunggi-do, one of the representative areas in Korea with a massive distribution of the low-income class. Based on the survey data, the level of housing defects were comparison analyzed per income decile (decile 1, decile 2, deciles 3–4), and per housing location, in the categories of subsidence, cracks in the wall, delamination, water leakage/infiltration, condensation, and contamination. The housing condition per income class was more defective in the decile 2 households rather than in the decile 2 households, and in the substructure more than in the superstructure. Among the six defects, contamination problems, caused by sub-standard living conditions, were the most frequent cases. Structural defects, subsidence and cracks in the wall, were found in the main living areas—the bedrooms and the living rooms. It was confirmed in this study that the conditions of low-income housing are serious, and that it is necessary to explore specific countermeasures in the near future.